Incidence and severity of reported acute sports injuries in 35 sports using insurance registry data - Åman, M.; Forssblad, M.; Henriksson-Larsen, K. (Scandinavian Journal of Medicine & Science in Sports, 2016)
Acute injuries in sport are still a problem where limited knowledge of incidence and severity in different sports at national level exists. In Sweden, 80% of the sports federations have their mandatory injury insurance for all athletes in the same insurance company and injury data are systematically kept in a national database. The aim of the study was to identify high-risk sports with respect to incidence of acute and severe injuries in 35 sports reported to the database. The number and incidences of injuries as well as injuries leading to permanent medical impairment (PMI) were calculated during 2008-2011. Each year approximately 12 000 injuries and 1 162 660 licensed athletes were eligible for analysis. Eighty-five percent of the injuries were reported in football, ice hockey, floorball, and handball. The highest injury incidence as well as PMI was in motorcycle, handball, skating, and ice hockey. Females had higher risk of a PMI compared with males in automobile sport, handball, floorball, and football. High-risk sports with numerous injuries and high incidence of PMI injuries were motorcycle, handball, ice hockey, football, floorball, and automobile sports. Thus, these sports ought to be the target of preventive actions at national level.